PENERAPAN METODE FORWARD CHAINING PADA SISTEM PAKAR UNTUK MENGATASI REJECT PAINTING SPARE PART OTOMOTIF DI PT ASTRA OTOPARTS TBK - Denny Riandhita Arief Permana; Septian Isnanto; Fifi Lailasari Hadianastuti; Zahra Nadhifa (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
P PT Astra Otoparts Tbk Divisi Nusametal is a company operating in the automotive industry. This company produces four-wheeled vehicle components, two-wheeled vehicle parts, and other automotive components made from aluminum materials. In the painting process, there is a quality inspection of the products divided into FG (Finish Good) and NG (Not Good) products. The use of technology can be very helpful in quality control, especially in the painting process. In the painting process, rejects often occur on automotive components. Each reject has different symptoms and causes, so the solution to address each reject is also different. Knowledge about solutions to address rejections is only possessed by the engineering team on the second shift, so handling can be delayed by 1 day and the painting process will be halted. The variables used are 13 symptoms and 51 causes. In this study, the use of the Forward Chaining method in the expert system can analyze reject symptoms and reject causes, allowing operators to identify the type of reject and fix the reject results without having to wait for engineering in the second shift. This way, repairs can be done in just 30-60 minutes, and operators can independently resolve 80% of painting reject issues while the painting process continues.